The main directions of transformation of modern global migration space and the place of Belarus in it - Zaharets, Uladzimir S.; Zaharets, Iryna V. (Journal of the Belarusian State University. Geography and Geology, 2017)
The article analyzes the current trends and processes of global migration space. Special attention is paid to the latest trends of legal and illegal migration in the European region. The basic factors determining international migration, its volume and geography. Noted that migrants from Eastern European countries enter the EU mainly on the basis of legally obtained residence permits, while immigrants from Africa and Asia primarily as political refugees. Migration is geographically localized. The place of the Republic of Belarus in the global migration space. We study the main directions of migration of human and labor resources of the country. Noted that contemporary global migration space country performs first the role of the donor or vendor of human and labor resources. The urgency of the development of complex medium and long-term measures to reduce the outflow of its own human and labor resources inother countries and attraction of these countries, a sufficient number of qualified workers.